STADIA PRADEWASA TUNGAU Macrocheies merdarius (AcARlNA: MACROCHELIDAE) Dl LABORATORIUM - Janita Aziz; Sri Hartini (BERITA BIOLOGI, 1997)
Maccrocheles mendAriUs are the abundant mite species found in poultry litter in Bogor Municipality. However, their potential as predators ofhouseflies eggs and larvae are yet not known. An effort to study their life cycle has been done in the laboratory with an hou/iy observation.The eggs and larvae could not be found whereas the pmtonymphal stAge Were 18.67 hours oh Average And deutonymphal Were 29.04hours.The average size of protonymphAl'stage were 33.97 X 24.53 /Urn And deutonymphal were 38.44 x 32.15 jum. All of these progeny were not known whether from the fertilized or unfertilized femAles.